2014
DOI: 10.1080/14693062.2014.912981
|View full text |Cite|
|
Sign up to set email alerts
|

Incremental CH4and N2O mitigation benefits consistent with the US Government's SC-CO2estimates

Abstract: Benefit-cost analysis can serve as an informative input into the policy-making process, but only to the degree it characterizes the major impacts of the regulation under consideration. Recently, the US, amongst other nations, has begun to use estimates of the social cost of CO 2 (SC-CO 2 ) to develop analyses that more fully capture the climate change impacts of GHG abatement. The SC-CO 2 represents the aggregate willingness to pay to avoid the damages associated with an additional tonne of CO 2 emissions. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 40 publications
(51 reference statements)
0
24
0
Order By: Relevance
“…The SC-CH 4 can also be estimated directly by the models used to estimate the SCC. Waldhoff et al (2014); (Marten et al 2014) and Marten and Newbold (2012) both found that the directly modeled relative damage of CH 4 to CO 2 was greater than the GWP-based damages. 16 Marten et al (2014) use a methodology consistent with the US Government SCC and the sensitivities tested in this paper and found that for CH 4 emissions in 2020, at a discount rate of 3 %, the Social Cost of Methane was (2007)$1200 (or $1302 in 2011$).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The SC-CH 4 can also be estimated directly by the models used to estimate the SCC. Waldhoff et al (2014); (Marten et al 2014) and Marten and Newbold (2012) both found that the directly modeled relative damage of CH 4 to CO 2 was greater than the GWP-based damages. 16 Marten et al (2014) use a methodology consistent with the US Government SCC and the sensitivities tested in this paper and found that for CH 4 emissions in 2020, at a discount rate of 3 %, the Social Cost of Methane was (2007)$1200 (or $1302 in 2011$).…”
Section: Resultsmentioning
confidence: 99%
“…16 Marten et al (2014) use a methodology consistent with the US Government SCC and the sensitivities tested in this paper and found that for CH 4 emissions in 2020, at a discount rate of 3 %, the Social Cost of Methane was (2007)$1200 (or $1302 in 2011$). The global ozone mortality benefits estimated in this paper are 0.7 or 1.5 times the estimate of climate benefits using the updated SCC and GWP, and 0.6 or 1.4 times the estimate of climate benefits from Marten et al (2014), for the short and long-term ozone mortality estimates, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This 'carrot-and-stick' approach can mitigate emissions at a rate faster than what conventional periodic LDAR surveys would allow. To illustrate, 'sticks' can take the form of fines or fees based on actual emission levels and a social cost of methane [29]; 'carrots' can include a system that rewards better-than-required performance (e.g. revenue recycling from fines or preferential permitting for excellent operators).…”
Section: Lessons For Future Mitigation Policiesmentioning
confidence: 99%